General quality of municipal education and the influences of public spending - Joyce Santana Bernardo; Fernanda Maria de Almeida; Ana Carolina Campana Nascimento (Arizona State University, 2020)
The purpose of this study was to quantify and evaluate the quality standard of education of Brazilian municipalities, by means of an indicator of the quality of municipal basic education, and to verify the relation between headings of the public educational budget and this quality of education. Through the Principal Components Analysis, the General Quality Index of Municipal Education (IQGEM) was created, which included micro and macrostructural aspects, between 2009 and 2013. Subsequently, an Inflation Beta Regression model was used to verify the relationships between the disaggregated educational budget and social factors and the IQGEM. Ranging from 0 (minimum) to 1 (maximum), the index showed an average quality of 0.61 points, being the highest values of municipalities in the South and Southeast. In addition, the factors that were positively related to the IQGEM were investments in school infrastructure and social aspects. On the other hand, expenses with personnel and consumables influenced it negatively. In general, these results indicate that investments in school infrastructure and social promotion policies are relevant to the quality of education in the municipalities of the country. On the other hand, although they have been negatively related to the IQGEM in the short term, it is possible that in the medium- and long-term investments in personnel and consumables can have positive influences.